Student’s Mathematical Literacy in Solving Asesmen Kompetensi Minimum Question in terms of Gender - Nimas Aufa; Janet Trineke Manoy (MATHEdunesa, 2022)
Mathematical literacy is the human ability to formulate, use, and interpret mathematical knowledge and skills in various real-life contexts. This descriptive qualitative study aims to describe the mathematical literacy of 4 grade XII students in solving the Asesmen Kompetensi Minimum (AKM) questions, in one of the Muhammadiyah Gresik High Schools based on gender. AKM is a basic assessment of students' abilities as a medium for developing self-competence so that they can think critically in everyday life. Collecting data using the AKM mathematical literacy test and interviews, test and interview data were analyzed based on indicators of mathematical literacy. The results showed that the literacy skills of female students met the indicators in the process of formulating, implementing, and interpreting problems with appropriate solutions. Meanwhile, male students met the indicators in the process of formulating and implementing. Teachers need to familiarize students with solving problems related to mathematical literacy.